2004
DOI: 10.1111/j.1745-4557.2004.tb00650.x
|View full text |Cite
|
Sign up to set email alerts
|

THE POTENTIAL OF TERMINALIA CATAPPA (TROPICAL ALMOND) SEED AS A SOURCE OF DIETARY PROTEIN

Abstract: The nutritional value of Tenninalia catappa seed as a source of dietaly protein was investigated. The crude protein content of the seed was high (25.81 %). The amino acid analysis showed a goodpattem of the essential amino acids (EAA) (in g/16 g N) -leucine (7.32). isoleucine (3.58), valine (2.74), phenylalanine (3.04). tryptophan (0.9), methionine (1.48), lysine (3.39), threonine {2.94), histidine (2.96). Tyrosine (2.12) is the limiting amino acid. The protein quality of the seed was evaluated by in vivo bioa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 12 publications
(7 reference statements)
3
23
1
Order By: Relevance
“…The protein content is similar to that of soybeans (40%) known for their high protein content (Obatolu, Osho, & Oyekan, 1993). Moreover, this protein level is about two times higher than those reported by various authors (Matos et al, 2009;Oduro et al, 2009;Oliveira et al, 2000;Ezeokonkwo & Dodson, 2004) that are between 22.1% and 29.4%. The fat content (50.66±1%) is similar to the values reported by Oleveira et al (2000) and Matos et al (2009), which are 58±029% and 51.80% respectively.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…The protein content is similar to that of soybeans (40%) known for their high protein content (Obatolu, Osho, & Oyekan, 1993). Moreover, this protein level is about two times higher than those reported by various authors (Matos et al, 2009;Oduro et al, 2009;Oliveira et al, 2000;Ezeokonkwo & Dodson, 2004) that are between 22.1% and 29.4%. The fat content (50.66±1%) is similar to the values reported by Oleveira et al (2000) and Matos et al (2009), which are 58±029% and 51.80% respectively.…”
Section: Discussioncontrasting
confidence: 45%
“…They also revealed the presence of saponins, glycosides, flavonoids, alkaloids, anthraquinones, anthraquinone glycosides, terpenoids and steroids (Oduro, Larbie, Amoako, & Antwi-Boasiako, 2009;Matos et al, 2009). The kernels of Terminalia catappa are good sources of proteins rich in essential amino acids (22-25%), lipids (35-52%), unsaturated fatty (oleic acid and linoleic acid), and minerals among which the most important are potassium (9280±0.14 mg/100 g), calcium (827.20±2.18 mg/100 g) and magnesium (798.6±0.32 mg/100 g) (Oduro et al, 2009;Matos et al, 2009;Ezeokonkwo & Dodson, 2004;Nwosu, Dosumu, & Okocha, 2008). Studies on the nutritional value and biological activity of the kernel of Terminalia catappa revealed that it has a good digestibility, exerts a strong antioxidant activity, possesses anti-HIV properties, anti-asthma properties, anti-inflammatory, anti-carcinogenic, antibacterial and hepatoprotective properties (AOAC, 1975;Dorsch & Wagner, 1991;Ko, Weng, & Chiou, 2002;Ko, Weng, Lin, & Chiou, 2003;Lin, Hsu, & Lin, 1999;Nagappa, Thakurdesai, Venkat, & Singh, 2003;Teotia & Singh, 1997;Atnasooriya & Dharmasiri, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Amino acid composition (Table 2) data suggest sulfur amino acids (methionine + cysteine) to be the first limiting amino acid, followed by lysine and threonine, in total seed proteins. Ezeokonkwo and Dodson [18] reported tyrosine, lysine, and methionine to be limiting amino acids in tropical almonds (Terminalia catappa). When FAO/WHO recommendations are followed, recalculation of data reported by Ezeokonkwo and Dodson indicates lysine to be the first limiting amino acid [Lys (3.39/5/80) = 0.584] in tropical almonds as chemical scores for Tyr + Phe (2.12 + 3.04 = 5.16)/6.30 = 0.819 and for Met + Cys (1.48 + 1.92 = 3.4)/3.5 = 0.971 no longer represent chemical scores consistent with first and second limiting amino acids.…”
Section: Chemical Compositionmentioning
confidence: 98%
“…In contrast, P. amygdalus was significantly (p<0.05) high in crude fats (50.96%) compared to T. catappa (43.71%) while there was no significant difference (p>0.05) between the protein contents of T. catappa (33.00%) and P. amygdalus (32.87%).The protein content of T. catappa (33.00%) in this study was higher than some data available in literature. The protein contents of T. catappa (33.00%) and P. amygdalus (32.89%) compared well and were even higher than the protein contents of most conventional oil seeds; for instance, groundnut (25.00%), black-eyed Ruhuna Journal of Science 74 Vol 9: 70-77, June 2018 beans (27.13%), brown beans (28.00%), cowpea (27.80%), bambara nuts (23.41%) and pigeon pea (21.88%), (Ezeokonkwo and Dodson 2007). According to Ezeoknkwo and Dodson (2007) the protein content of T. catappa was 25.81%.…”
Section: Proximate Compositionmentioning
confidence: 99%
“…They reported T. catappa seeds to be rich in protein and could reduce the level of malnutrition in most impoverished countries of Africa and hence encouraged its use in food supplements either in raw or roasted form to improve the food nutrient content. Ezeokonkwo and Dodson (2007) reported the potential of T. catappa seed as a source of dietary protein. Olatidoye et al (2011) examined the chemical composition and physicochemical characteristics of Tropical Almond nuts (T. catappa L.) cultivated in south western Nigeria and reported that the physicochemical properties of the almond seed oil indicated that it is edible, drying and suggested its suitability for industrial purposes as well as the nutritional potentials of the nut, which could serve as an alternative food ingredient for unsaturated vegetable oil.…”
Section: Introductionmentioning
confidence: 99%